A model of atherosclerosis using nicotine with balloon overdilation in a porcine - Munki Kim (Nature Portfolio, 2021)
Abstract Pigs are important experimental animals for cardiovascular research. Few porcine coronary atherosclerosis models have been developed; however, their induction requires more than six months. We developed a porcine coronary artery atherosclerosis model using nicotine injection with a balloon overdilation. A coronary balloon was placed in the porcine coronary artery and overdilated to induce a mechanical injury. Nicotine was administrated via intramuscular injection every day, and changes in the coronary artery were observed after four weeks. Coronary angiography revealed nicotine injection with a balloon overdilation group showed narrowing of the coronary artery at the injury site. The combination of balloon and nicotine significantly increased the intimal hyperplasia in optical coherence tomography analysis. Proliferated tunica media were noted in the nicotine injection with balloon overdilation groups and lack of collagen was observed in the tunica media at eight weeks. Quantitative analysis showed increased smooth muscle actin alpha (SMA), cluster of differentiation 68 (CD68), and Krüppel-like factor 4 (KLF4) in the nicotine injection with balloon overdilation groups. Immunohistochemistry results showed CD68-positive cells displayed SMA- and KLF4-positive reactivity in the border zone of the intimal hyperplasia. Our results show that nicotine injection with balloon overdilation can induce atherosclerotic lesions within one month, which can serve as an alternative pig animal model for the development of coronary stents.